2021
DOI: 10.1021/acs.est.1c02023
|View full text |Cite
|
Sign up to set email alerts
|

Organic Components of Personal PM2.5 Exposure Associated with Inflammation: Evidence from an Untargeted Exposomic Approach

Abstract: Fine particulate matter (PM2.5) can promote chronic diseases through the fundamental mechanism of inflammation; however, systemic information is lacking on the inflammatory PM2.5 components. To decipher organic components from personal PM2.5 exposure that were associated with respiratory and circulatory inflammatory responses in older adults, we developed an exposomic approach using trace amounts of particles and applied it on 424 personal PM2.5 samples collected in a panel study in Beijing. Applying an integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Levels of 2-MePHE and PHE, together with another 15 PAHs (Table S1 in the Supporting Information), in personal PM 2.5 samples were measured with GC-time-of-flight-MS (GC-ToF-MS, Agilent 7890B-7200) as described previously . Briefly, a punch of each filter (3 mm i.d.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of 2-MePHE and PHE, together with another 15 PAHs (Table S1 in the Supporting Information), in personal PM 2.5 samples were measured with GC-time-of-flight-MS (GC-ToF-MS, Agilent 7890B-7200) as described previously . Briefly, a punch of each filter (3 mm i.d.)…”
Section: Methodsmentioning
confidence: 99%
“…22 Levels of 2-MePHE and PHE, together with another 15 PAHs (Table S1 in the Supporting Information), in personal PM 2.5 samples were measured with GC-time-of-flight-MS (GC-ToF-MS, Agilent 7890B-7200) as described previously. 8 Briefly, a punch of each filter (3 mm i.d.) was loaded into a microvial and spiked with 0.5 ng of deuterated PAHs as the internal standard and afterward was inserted into the GC injection port for thermal desorption and separation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive two-dimensional gas chromatography has been proven to be a more powerful tool for analyzing complex trace chemicals than traditional one-dimensional gas chromatography due to the combination of two columns with different separation mechanisms. The large amounts of organic compounds in the air would cause a massive data processing problem. Multivariate chemometric methods have brought about great progress in simplifying data and quickly extracting the information with differences among different sample groups. Therefore, it is feasible to combine comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry (GC×GC-TOFMS) with chemometrics to filter chemicals with markedly different proportions in the gas phase and size-fractionated particle phases. The human intakes through inhalation and dermal exposure to identified compounds could be estimated using the International Commission on Radiological Protection deposition model and transdermal permeability model, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While understanding of the social and environmental factors that affect sleep is growing, less is known regarding the effects of chemical pollutants such as pesticides, heavy metals, solvents, and endocrinedisrupting chemicals (EDCs) on sleep health. Chemical pollutants have been shown to affect neurotransmitter systems and other sleep-relevant processes such as inflammation [53][54][55]. For example, animal and in vitro studies have shown that lead exposure alters GABA release [56], and a study in monkeys reported that treatment with lead during infancy caused insomnia [57].…”
Section: Introductionmentioning
confidence: 99%